Abrasion-resistant coating for deep sea environment and preparation method of abrasion-resistant coating

By using atomic layer deposition technology to deposit the alumina sealed layer on the amorphous carbon composite coating, the problem of insufficient abrasion resistance of the coating in deep-sea environment is solved, and the high density and lubricity are improved, which significantly reduces the Corrosion and wear rate.

CN119243153APending Publication Date: 2025-01-03NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411276315.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The wear resistance of traditional hard protective coating materials and polymer coatings in deep-sea environments is reduced, making it difficult to meet the protection needs of key metal components. The amorphous carbon-based coating has growth defects in seawater, resulting in the failure of the coating interface. Inadequate abrasive performance.

Method used

Atomic layer deposition technology is used to deposit an alumina sealing layer on the amorphous carbon composite coating to fill internal defects and form a dense composite friction film to improve the corrosion resistance and lubrication performance of the coating.

Benefits of technology

It significantly reduces the porosity and defect density of the coating, improves the abrasion resistance and lubricity, reduces the corrosion current density and wear rate in deep-sea environments, and improves the abrasion resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243153A_ABST
    Figure CN119243153A_ABST
Patent Text Reader

Abstract

The invention provides an abrasion-resistant coating for a deep sea environment and a preparation method of the abrasion-resistant coating, and relates to the technical field of surface treatment. The abrasion-resistant coating comprises an amorphous carbon composite coating body and an aluminum oxide hole sealing layer, the aluminum oxide hole sealing layer is deposited on the amorphous carbon composite coating body through the atomic layer deposition technology and fills up internal defects of the amorphous carbon composite coating body, and the thickness of the aluminum oxide hole sealing layer is 25 nm to 120 nm; according to the wear-resistant coating provided by the invention, the amorphous carbon composite coating is subjected to hole sealing treatment through an atomic layer deposition technology, so that the porosity of the wear-resistant coating is reduced, channels for seawater to diffuse into a matrix are reduced, and the corrosion resistance of the coating is improved; by optimizing the thickness of the aluminum oxide hole sealing layer, a compact composite friction film which takes amorphous carbon as a main phase and is compounded with Al2O3 nanoclusters can be formed in the friction process, and the problem that a relatively loose friction film of a graphite-like structure is formed in the abrasion process of a traditional carbon-based coating, and consequently the abrasion resistance of the deep sea environment is insufficient is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of surface treatment, and in particular to an abrasion-resistant coating for deep-sea environment and a preparation method thereof. Background Art

[0002] The development of the marine economy cannot be separated from the support of marine engineering equipment, such as ship propeller bearings, submarine buoyancy adjustment systems, underwater robot joints, seawater hydraulic system plunger pumps, deep-sea drilling heave compensation devices and other key moving parts of marine engineering equipment. These key metal parts face accelerated damage under harsh working conditions such as high hydrostatic pressure and abrasion in the deep-sea environment, which directly threatens the service safety of marine engineering equipment.

[0003] The wear resistance of traditional hard protective coating materials and polymer coatings will be significantly reduced in deep-sea environments, making it difficult to meet the protection needs of key metal parts. Amorphous carbon coating (also known as diamond-like carbon, DLC for short) is an amorphous film. Due to its high hardness and high elastic modulus, low friction coefficient and excellent chemical inertness, it has broad application prospects as a protective coating for key moving parts of marine engineering equipment.

[0004] The wear resistance of amorphous carbon-based coatings is closely related to the density of the coatings. Generally, amorphous carbon-based coatings prepared by physical vapor deposition (PVD) inevitably have growth defects during the deposition process, including nodule defects, pinhole defects, and through-type defects. Amorphous carbon-based coatings are sufficiently chemically inert in seawater, but there are still many inherent growth defects in the coatings. Seawater can penetrate into the substrate through coating defects, causing local corrosion of the metal at the defects, especially in deep-sea environments, where high hydrostatic pressure accelerates the seawater penetration process, leading to coating interface failure and significantly reduced wear resistance.

[0005] The existing multi-layer coating structure design and high-power pulsed magnetron sputtering technology can reduce the defect density of amorphous carbon-based coatings to a certain extent through multi-interface barriers or increased plasma density, but it is still difficult to overcome the technical problem of insufficient coating density caused by the PVD sputtering process. In addition, during the abrasion process, a relatively loose graphite-like structure friction film will be formed on the surface of the amorphous carbon film in the contact area of ​​the friction pair, resulting in insufficient wear resistance of the coating. Summary of the invention

[0006] In view of the deficiencies of the prior art, the present invention provides a wear-resistant coating for use in a deep-sea environment and a preparation method thereof. The prepared wear-resistant coating has both excellent wear resistance and lubrication properties.

[0007] The present invention provides a wear-resistant coating for deep-sea environment, wherein the wear-resistant coating comprises an amorphous carbon composite coating and an alumina sealing layer, wherein the alumina sealing layer is deposited on the amorphous carbon composite coating by atomic layer deposition technology and fills the internal defects of the amorphous carbon composite coating, and the thickness of the alumina sealing layer is 25-120 nm.

[0008] The wear-resistant coating for deep-sea environment provided by the present invention performs pore sealing treatment on the amorphous carbon composite coating by atomic layer deposition (ALD), thereby reducing the porosity of the wear-resistant coating and reducing the channels for seawater to diffuse into the substrate. Compared with PVD (physical vapor deposition) technology, the present invention adopts ALD (atomic layer deposition) alumina pore sealing layer, which is deposited layer by layer in the pores of the amorphous carbon composite coating by chemical reaction, thereby reducing the introduction of impurities and defects during the deposition process, and the deposited alumina pore sealing layer has higher density, which can more effectively prevent the diffusion of corrosive substances and improve the corrosion resistance of the coating; but When the thickness of the alumina sealing layer is less than 25nm, the sealing effect of the amorphous carbon composite coating is not obvious, and it is difficult to hinder the high hydrostatic pressure from accelerating the penetration of seawater. At the same time, in the contact area of ​​the friction pair, an appropriate amount of Al2O3 nanoclusters cannot be formed in the friction film to improve its density and play a high load-bearing and lubricating role; when the thickness of the alumina sealing layer is greater than 120nm, the friction process mainly reflects the Al2O3 friction and wear characteristics, and it is impossible to form a composite friction film with amorphous carbon as the main phase and composite Al2O3 nanoclusters, and it is difficult to give full play to the wear resistance and lubrication advantages of the amorphous carbon composite coating. The wear-resistant coating for deep-sea environment provided by the present invention, when the thickness of the alumina sealing layer is in the range of 25-120nm, can form a dense composite friction film with amorphous carbon as the main phase and composite Al2O3 nanoclusters with the amorphous carbon composite coating in the contact area of ​​the friction pair during the friction process, which plays a high load-bearing and lubricating role, can significantly reduce the friction coefficient and wear rate of the coating, improve the wear resistance of the coating in the deep-sea environment, and solve the problem that traditional carbon-based coatings form a relatively loose graphite-like structure friction film during the abrasion process, resulting in insufficient wear resistance in the deep-sea environment.

[0009] In a possible implementation, the amorphous carbon composite coating includes: a first metal layer and a nitride layer of the first metal sequentially deposited on the substrate; Iterative layers of an amorphous carbon layer and a second metal layer deposited on the nitride layer of the first metal, the number of the iterative layers being ≥ 6; an amorphous carbon functional layer deposited on the iterative layer; The metals in the first metal layer, the first metal nitride layer and the second metal layer are carbide-forming elements.

[0010] The above-mentioned amorphous carbon composite coating can, on the one hand, ensure that during the friction process, in the contact area of ​​the friction pair, the alumina sealing layer and the amorphous carbon composite coating form a dense composite friction film with amorphous carbon as the main phase and composite Al2O3 nanoclusters. On the other hand, the excellent deep-sea corrosion resistance of the amorphous carbon composite coating can be used to further enhance the long-term corrosion resistance of the wear-resistant coating in the deep-sea environment.

[0011] Further, the metal in the first metal layer, the first metal nitride layer and the second metal layer is at least one of Cr, W, Ti, Ta, Zr, V and Nb.

[0012] Furthermore, the thickness of the first metal layer and the first metal nitride layer is 120-180 nm.

[0013] Furthermore, the thickness of the amorphous carbon layer is 70-90 nm.

[0014] Furthermore, the thickness of the second metal layer is 90-110 nm.

[0015] Furthermore, the thickness of the amorphous carbon functional layer is 230-250 nm.

[0016] Furthermore, the substrate is any one of 17-4 PH stainless steel, S32205 duplex stainless steel and AISI 4140 alloy steel.

[0017] The present invention also provides a method for preparing the above-mentioned wear-resistant coating for deep-sea environment, comprising the following steps: S1. In an inert gas atmosphere, sputtering a metal target of a carbide-forming element, depositing a first metal layer on a substrate, and then introducing nitrogen to form a first metal layer / a nitride layer of the first metal; S2, sputtering a graphite target in an inert gas atmosphere to deposit an amorphous carbon layer on the first metal nitride layer in step S1; closing the graphite target, opening the metal target, and depositing a second metal layer on the amorphous carbon layer in an inert gas atmosphere, repeatedly sputtering the graphite target and the metal target to form an iterative layer of amorphous carbon layer / second metal layer; S3, sputtering the graphite target in an inert gas atmosphere to deposit an amorphous carbon functional layer on the iterative layer in step S2 to obtain an amorphous carbon composite coating; S4. Using atomic layer deposition technology, deposit an aluminum oxide sealing layer on the amorphous carbon composite coating in step S3. The aluminum oxide sealing layer fills the internal defects of the composite coating to obtain a wear-resistant coating for deep-sea environment.

[0018] The preparation method of the wear-resistant coating provided by the present invention adopts atomic layer deposition technology to deposit an aluminum oxide sealing layer on the surface of the amorphous carbon composite coating, which plays a role in sealing defects, significantly reduces the defect density in the amorphous carbon composite coating, reduces the porosity of the amorphous carbon composite coating, and improves the density, wear resistance and lubricity of the amorphous carbon composite coating.

[0019] In a possible implementation manner, the sputtering in steps S1, S2 and S3 is performed by direct current magnetron sputtering.

[0020] In a possible implementation manner, the inert gas in step S1 is any one of helium, neon, argon, krypton and xenon.

[0021] In a possible implementation manner, the substrate in step S1 is first etched before the first metal layer is deposited. The etching process is as follows: in an inert gas atmosphere, an ion source is used to etch the substrate for 10-50 minutes. The current of the ion source is 0.1-0.4 A. The gas pressure of the etching chamber is 1.5-4.5×10 -5 Torr or less, the flow rate of the inert gas is 25-43 sccm, and the negative bias voltage of the substrate is 50-250 V.

[0022] In a possible embodiment, the deposition process of the first metal layer / first metal nitride layer in step S1 is: the power supply power of the metal target is 1.5-3.5kW, the flow rate of the inert gas is 45-65sccm, the deposition chamber pressure is 1.9-2.1mTorr, the negative bias voltage of the substrate is 100-200V, and the deposition temperature is 120-200°C.

[0023] In a possible implementation, the deposition process of the amorphous carbon layer in step S2 is: the power supply current of the graphite target is 2.5-3.5A, the deposition chamber pressure is 1.9-2.4 mTorr, the negative bias voltage of the substrate is 100-200V, the flow rate of the inert gas is 50-65sccm, and the deposition time is 3-5min.

[0024] In a possible implementation, the deposition process of the second metal layer in step S2 is: the power supply power of the metal target is 2-3kW, the power supply current is 2.5-3.5A, the deposition chamber pressure is 1.9-2.1mTorr, the negative bias voltage of the substrate is 100-200 V, the flow rate of the inert gas is 50-65sccm, and the deposition time is 4-6min.

[0025] In a possible implementation manner, the number of repetitions in step S2 is 6-30 times.

[0026] In a possible implementation, the deposition process of the amorphous carbon functional layer in step S3 is as follows: the current of the graphite target is 2.5-3.5A, the flow rate of the inert gas is 50-55sccm, the deposition chamber pressure is 1.9-2.1mTorr, the negative bias voltage of the substrate is 100-200V, and the deposition temperature is room temperature.

[0027] In a possible embodiment, the deposition process of the aluminum oxide sealing layer in step S4 is as follows: in an atomic layer deposition system in which the amorphous carbon composite coating is placed, a dry inert gas, a gaseous precursor, a dry inert gas, water vapor, and a dry inert gas are sequentially introduced in a single deposition cycle, wherein the precursor is trimethylaluminum or tetraisopropyl titanate, and the deposition cycle is repeated 100-500 times. In the deposition process of the aluminum oxide sealing layer, the purpose of the first introduction of the dry inert gas is to purge the residual gas in the previous step in the chamber to make the deposited ALD coating purer, and then the gaseous precursor is introduced, and the gaseous precursor will be adsorbed on the surface of the substrate; the dry inert gas is introduced for the second time to purge the residual gas in the chamber and the gaseous precursor that is not firmly adsorbed; then water vapor is introduced to react chemically with the gaseous precursor adsorbed on the surface of the substrate to form an Al2O3 film; and then the dry inert gas is introduced for the third time to purge the excess water vapor in the chamber. The aluminum oxide sealing layer deposited by the above deposition process has fewer impurities and defects and higher density, so that the prepared coating has better anti-abrasion performance.

[0028] Furthermore, the dry inert gas is nitrogen or argon.

[0029] Furthermore, the time for introducing the dry inert gas for the first time is 3-6s.

[0030] Furthermore, the introduction time of the gaseous precursor is 6-9s. By controlling the introduction time of the gaseous precursor, the thickness of the ALD sealing coating in a single cycle can be controlled to avoid the excessive thickness of the sealing coating in a single cycle due to too long introduction time, which leads to stress concentration in the coating and even peeling of the coating; if the introduction time is too short, the thickness in a single cycle will be too small, which will slow down the deposition speed and increase the cost.

[0031] Furthermore, the time for introducing the dry inert gas for the second time is 4-5s.

[0032] Furthermore, the water vapor is introduced for a time of 1-4 s; Furthermore, the time for introducing the dry inert gas for the third time is 2-5s.

[0033] The above-mentioned implementation modes can be combined arbitrarily based on the common sense in the art.

[0034] The reagents and raw materials used in the present invention are commercially available.

[0035] The positive and progressive effects of the present invention are: The wear-resistant coating for deep-sea environment and its preparation method provided by the present invention play the role of sealing defects by depositing an ALD alumina sealing layer on the surface of the amorphous carbon composite coating, significantly reducing the defect density in the amorphous carbon composite coating, reducing the porosity of the amorphous carbon composite coating, and improving the compactness of the amorphous carbon composite coating. Compared with the unsealed amorphous carbon composite coating, the internal defects are effectively reduced, and the porosity is reduced by 3 orders of magnitude, thereby blocking the diffusion path of the corrosive medium entering the interior. The surface ALD alumina sealing layer has excellent lubricity, and forms a dense friction film of alumina composite amorphous carbon during the abrasion process, which plays the role of reducing wear and lubrication, and has excellent anti-wear performance in deep-sea environment. In a simulated deep-sea environment, compared with the unsealed amorphous carbon composite coating, the corrosion current density is reduced by 3 orders of magnitude, the friction coefficient is reduced by 20%, and the wear rate is reduced by 1 order of magnitude. The wear-resistant coating provided by the present invention has excellent wear resistance and lubrication performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 A schematic diagram of a sealing process provided for a specific embodiment of the present invention.

[0037] Figure 2 This is a graph showing the results of potentiodynamic polarization tests on the wear-resistant coatings prepared in Example 1, Comparative Example 1, and Comparative Example 2.

[0038] Figure 3 This is a graph showing the results of constant potential polarization tests of the wear-resistant coatings prepared in Example 1, Comparative Example 1, and Comparative Example 2.

[0039] Figure 4 This is the surface morphology of the wear-resistant coating prepared in Example 1 after polarization corrosion.

[0040] Figure 5 This is the surface morphology of the wear-resistant coating prepared in Comparative Example 1 after polarization corrosion.

[0041] Figure 6 This is the surface morphology of the wear-resistant coating prepared in Comparative Example 2 after polarization corrosion.

[0042] Figure 7 This is a graph showing the friction coefficient results of the wear-resistant coatings prepared in Example 1, Comparative Example 1, and Comparative Example 2.

[0043] Figure 8 This is a data chart of the wear rate of the wear-resistant coatings prepared in Example 1, Comparative Example 1, and Comparative Example 2. DETAILED DESCRIPTION

[0044] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0045] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0046] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0047] Example 1

[0048] This embodiment provides an abrasion-resistant coating for deep-sea environment, which is prepared by the following preparation method: (1) 17-4 PH stainless steel was selected as the substrate, and the substrate was ultrasonically cleaned in acetone and ethanol. After the substrate was dried, it was placed in a vacuum chamber and fixed on a workpiece bracket. The vacuum chamber was evacuated to 1.5×10 -5 Torr or less, then under the conditions of argon gas flow rate of 43 sccm and bias voltage of -250 V, turn on the ion source, adjust the ion source current to 0.4 A, and use argon plasma to etch the substrate surface for 50 min; (2) Argon gas was introduced into the chamber with a flow rate of 65 sccm. DC magnetron sputtering technology was used to maintain the pressure in the vacuum chamber at 2.0 mTorr. The DC power supply connected to the chromium sputtering target was turned on, and the power frequency was set to 350 Hz, the power current was 2.5 A, the substrate bias was -150 V, and the deposition temperature was 200 °C. The chromium metal layer was deposited. After the deposition of the chromium metal layer, nitrogen and argon gas were introduced with a flow rate of 25 sccm for nitrogen and 55 sccm for argon. The pressure in the reaction chamber was 2.2 mTorr. The other parameters remained unchanged. The chromium nitride layer was deposited. The thickness of the chromium metal layer / chromium nitride layer was 150 nm in total. The temperature was then lowered to room temperature. (3) Continue to introduce argon gas into the chamber, the flow rate of argon gas is 65 sccm, use DC magnetron sputtering technology, maintain the pressure in the vacuum chamber at 2.4 mTorr, turn on the DC power supply connected to the graphite sputtering target, set the power supply current to 3.0 A, the substrate bias voltage to -200 V, the deposition temperature to room temperature, deposit the amorphous carbon layer for 4 minutes, and the thickness of the amorphous carbon layer is 80 nm; (4) Continue to introduce argon gas into the chamber at a flow rate of 65 sccm. Use DC magnetron sputtering technology to maintain the chamber pressure at 2.0 mTorr. Turn on the DC power supply connected to the chromium sputtering target and set the power supply current to 3.5 A. The bias voltage of the substrate is -100 V. The deposition temperature is room temperature. The chromium metal layer is deposited for 5 minutes. The thickness of the chromium metal layer is 100 nm. (5) repeating steps (3) and (4) to alternately deposit amorphous carbon layers and chromium metal layers for 30 cycles; (6) Continue to introduce argon gas into the chamber, the flow rate of argon gas is 55 sccm, adopt DC magnetron sputtering technology, maintain the chamber pressure at 2.0 mTorr, turn on the DC power supply connected to the graphite sputtering target, set the power supply current to 3.0 A, the substrate bias voltage to -200 V, the deposition temperature to room temperature, deposit an amorphous carbon functional layer, the thickness of the amorphous carbon functional layer is 250 nm, and obtain an amorphous carbon composite coating; (7) The prepared amorphous carbon composite coating was placed in an atomic layer deposition chamber. Nitrogen was introduced for 6 seconds, trimethylaluminum for 9 seconds, nitrogen for 4 seconds, water vapor for 1 second, and nitrogen for 2 seconds in a single cycle. The deposition was repeated for 300 cycles. The thickness of the ALD sealing layer was 70 nm, and a wear-resistant coating for deep-sea environments was obtained.

[0049] In a simulated 1500m deep sea environment, the wear-resistant coating for deep sea environment prepared in Example 1 was tested, and the corrosion current density was 1.39×10 -9 A / cm 2 After corrosion, the coating porosity is 0.25%, the friction coefficient is 0.062, and the wear rate is about 2.3×10 -9 mm 3 / Nm.

[0050] Example 2

[0051] This embodiment provides an abrasion-resistant coating for deep-sea environment, which is prepared by the following preparation method: (1) S32205 duplex stainless steel was selected as the substrate, and the substrate was ultrasonically cleaned in acetone and ethanol. After the substrate was dried, it was placed in a vacuum chamber and fixed on a workpiece bracket. The vacuum chamber was evacuated to 4.5×10 -5 Torr or less, then under the conditions of krypton gas flow rate of 25 sccm and negative bias voltage of -50 V, turn on the ion source, adjust the ion source current to 0.1 A, and use krypton plasma to etch the substrate surface for 10 minutes; (2) Krypton gas was introduced into the chamber at a flow rate of 45 ccm. DC magnetron sputtering technology was used to maintain the chamber pressure at 1.9 mTorr. The DC power supply connected to the chromium sputtering target was turned on, and the power frequency was set to 350 Hz, the current was 2.5 A, the substrate bias was -100 V, and the deposition temperature was 120 °C. The chromium metal layer was deposited. Nitrogen and krypton gas were introduced at a nitrogen flow rate of 20 sccm and a krypton flow rate of 50 sccm. The reaction chamber pressure was 2.1 mTorr. The other parameters remained unchanged. A chromium nitride transition layer was deposited. The thickness of the chromium / chromium nitride strong bonding gradient layer was 120 nm in total. The temperature was then lowered to room temperature. (3) Continue to introduce krypton gas into the chamber at a flow rate of 50 sccm. Use DC magnetron sputtering technology to maintain the chamber pressure at 1.9 mTorr. Turn on the DC power supply connected to the graphite sputtering target and set the power supply current to 2.5 A. The bias voltage of the substrate is -100 V. The deposition temperature is room temperature. Deposit an amorphous carbon layer for 3 minutes with a thickness of 70 nm. (4) Continue to introduce krypton gas into the chamber at a flow rate of 50 sccm. Use DC magnetron sputtering technology to maintain the chamber pressure at 1.9 mTorr. Turn on the DC power supply connected to the chromium sputtering target and set the power supply current to 2.5 A. The bias voltage of the substrate is -100 V. The deposition temperature is room temperature. The chromium metal layer is deposited for 4 minutes. The thickness of the chromium metal layer is 90 nm. (5) Repeating steps (3) and (4) to alternately deposit amorphous carbon layers and chromium metal layers for 6 cycles; (6) Continue to introduce krypton gas into the cavity, the krypton gas flow rate is 50 sccm, use DC magnetron sputtering technology, maintain the cavity pressure at 1.9 mTorr, turn on the DC power supply connected to the graphite sputtering target, set the current to 2.5 A, the substrate bias voltage to -100 V, the deposition temperature to room temperature, deposit an amorphous carbon functional layer, the thickness of the amorphous carbon functional layer is 230 nm, and obtain an amorphous carbon composite coating; (7) The prepared amorphous carbon composite coating was placed in an atomic layer deposition chamber. Argon gas was introduced for 4 s, trimethylaluminum for 7 s, argon gas for 5 s, water vapor for 4 s, and argon gas for 5 s in a single cycle. The deposition was repeated for 100 cycles. The thickness of the ALD sealing layer was 25 nm, and a wear-resistant coating for deep-sea environments was obtained.

[0052] In a simulated 1500m deep sea environment, the wear-resistant coating for deep sea environment prepared in Example 2 was tested, and the corrosion current density was 7.3×10 -8 A / cm 2 After corrosion, the coating porosity is 1.1%, the friction coefficient is 0.070, and the wear rate is 7.5×10 -9 mm 3 / Nm.

[0053] Example 3

[0054] This embodiment provides an abrasion-resistant coating for deep-sea environment, which is prepared by the following preparation method: (1) AISI4140 ultra-high strength low alloy steel was selected as the substrate, and the substrate was ultrasonically cleaned in acetone and ethanol. After the substrate was dried, it was placed in a vacuum chamber and fixed on the workpiece bracket. The vacuum chamber was evacuated to 3.0×10 -5 Torr or less, then under the conditions of argon gas flow rate of 40 sccm and bias voltage of -200 V, turn on the ion source, adjust the ion source current to 0.2 A, and use argon plasma to etch the substrate surface for 40 minutes; (2) Argon gas was introduced into the chamber with a flow rate of 50 sccm. DC magnetron sputtering technology was used to maintain the chamber pressure at 2.1 mTorr. The DC power supply connected to the chromium sputtering target was turned on, and the power frequency was set to 350 Hz, the current was 3 A, the substrate bias was -200 V, and the deposition temperature was 180 ° C. The chromium metal layer was deposited. After the deposition of the chromium metal layer, nitrogen and argon gas were introduced with a flow rate of 25 sccm for nitrogen and 50 sccm for argon. The reaction chamber pressure was 2.3 mTorr. The other parameters remained unchanged. The chromium nitride layer was deposited. The thickness of the chromium metal layer / chromium nitride layer was 180 nm in total, and the temperature was lowered to room temperature. (3) Continue to introduce argon gas into the chamber at a flow rate of 50 sccm. Use DC magnetron sputtering technology to maintain the chamber pressure at 2.1 mTorr. Turn on the DC power supply connected to the graphite sputtering target, set the power supply current to 3.5 A, the substrate bias voltage to -200 V, the deposition temperature to room temperature, and deposit the amorphous carbon layer for 5 minutes. The thickness of the amorphous carbon layer is 90 nm. (4) Continue to introduce argon gas into the chamber at a flow rate of 50 sccm. Use DC magnetron sputtering technology to maintain the chamber pressure at 2.1 mTorr. Turn on the DC power supply connected to the chromium sputtering target, set the power supply current to 3 A, the substrate bias voltage to -200 V, the deposition temperature to room temperature, and deposit the chromium metal layer for 6 minutes. The thickness of the chromium metal layer is 110 nm. (5) repeating steps (3) and (4) to alternately deposit amorphous carbon layers and chromium metal layers for 25 cycles; (6) Continue to introduce argon gas into the chamber at a flow rate of 50 sccm. Use DC magnetron sputtering technology to maintain the chamber pressure at 2.1 mTorr. Turn on the DC power supply connected to the graphite sputtering target, set the power supply current to 3.5 A, the substrate bias voltage to -200 V, and the deposition temperature to room temperature to deposit an amorphous carbon functional layer with a thickness of 250 nm. (7) The prepared amorphous carbon composite coating was placed in an atomic layer deposition chamber, and nitrogen was introduced in sequence for 3 seconds, tetraisopropyl titanate for 6 seconds, nitrogen for 4 seconds, water vapor for 1 second, and nitrogen for 2 seconds. The deposition was repeated for 500 cycles. The thickness of the ALD sealing layer was 120 nm, and a wear-resistant coating for deep-sea environments was obtained.

[0055] In a simulated 1500 m deep sea environment, the wear-resistant coating for deep sea environment prepared in Example 3 was tested, and the corrosion current density was 6.33×10 -8 A / cm 2 After corrosion, the coating porosity is 0.21%, the friction coefficient is 0.068, and the wear rate is 5.9×10 -9 mm 3 / Nm.

[0056] Comparative Example 1 As a comparative example of Example 1, the preparation method of the coating provided in Comparative Example 1 is as follows: (1) 17-4 PH stainless steel was selected as the substrate, and the substrate was ultrasonically cleaned in acetone and ethanol. After the substrate was dried, it was placed in a vacuum chamber and fixed on a workpiece bracket. The vacuum chamber was evacuated to 4.5×10 -5 Torr or less, then under the conditions of neon gas flow rate of 45 sccm and bias voltage of -250 V, turn on the ion source, adjust the ion source output voltage to 1200 V, and use neon plasma to etch the substrate surface for 40 minutes; (2) Neon gas was introduced into the chamber at a flow rate of 65 sccm. DC magnetron sputtering technology was used to maintain the chamber pressure at 2.4 mTorr. The DC power supply connected to the chromium sputtering target was turned on, and the power frequency was set to 350 Hz, the power current to 3.5 A, the substrate bias voltage to -200 V, and the deposition temperature to 200 °C. A chromium metal layer was deposited. Nitrogen gas was introduced at a flow rate of 30 sccm. The other parameters remained unchanged. A chromium nitride layer was deposited. The total thickness of the chromium metal layer / chromium nitride layer was 190 nm. The temperature was then lowered to room temperature. (3) Continue to introduce neon gas into the chamber at a flow rate of 65 sccm. Use DC magnetron sputtering technology to maintain the chamber pressure at 2.5 mTorr. Turn on the DC power supply connected to the graphite sputtering target, set the power supply current to 3.5 A, the substrate bias voltage to -250 V, and the deposition temperature to room temperature to deposit an amorphous carbon layer with a thickness of 100 nm. (4) Continue to introduce neon gas into the chamber at a flow rate of 65 sccm. Use DC magnetron sputtering technology to maintain the chamber pressure at 2.4 mTorr. Turn on the DC power supply connected to the chromium sputtering target. Set the power supply current to 4.0 A. Set the substrate bias voltage to -150 V. Set the deposition temperature to room temperature. Deposit a chromium metal layer with a thickness of 120 nm. (5) repeating steps (3) and (4) to alternately deposit amorphous carbon layers and chromium metal layers for 30 cycles; (6) Continue to introduce neon gas into the chamber at a flow rate of 65 sccm. Use DC magnetron sputtering technology to maintain the chamber pressure at 2.4 mTorr. Turn on the DC power supply connected to the graphite sputtering target and set the current to 3.5 A. The bias voltage of the substrate is -250 V. The deposition temperature is room temperature. Deposit an amorphous carbon functional layer with a thickness of 280 nm.

[0057] In a simulated 1500m deep sea environment, the coating prepared in Comparative Example 1 was tested, and the corrosion current density was 9.25×10 -7 A / cm 2 After corrosion, the coating porosity is 3.44%, the friction coefficient is 0.078, and the wear rate is about 1.1×10 -8 mm 3 / Nm.

[0058] Comparative Example 2 The preparation method of the coating provided in Comparative Example 2 is as follows: (1) 17-4 PH stainless steel was selected as the substrate, and the substrate was ultrasonically cleaned in acetone and ethanol. After the substrate was dried, it was placed in a vacuum chamber and fixed on a workpiece bracket. The vacuum chamber was evacuated to 1.5×10 -5Torr or less, then under the conditions of xenon gas flow rate of 25 sccm and bias voltage of -50 V, turn on the ion source, adjust the output voltage to 1200 V, and use xenon plasma to etch the substrate surface for 30 minutes; (2) Xenon gas was introduced into the cavity at a flow rate of 45 sccm. DC magnetron sputtering technology was used to maintain the cavity pressure at 1.8 mTorr. The DC power supply connected to the chromium sputtering target was turned on, and the power frequency was set to 350 Hz, the power current was 3.0 A, the substrate bias was -50 V, and the deposition temperature was 100 °C. A chromium metal layer was deposited. Nitrogen gas was introduced at a flow rate of 15 sccm. The other parameters remained unchanged. A chromium nitride layer was deposited. The thickness of the chromium metal layer / chromium nitride layer was 130 nm in total. The temperature was then lowered to room temperature. (3) Continue to introduce xenon gas into the chamber at a rate of 45 sccm. Use DC magnetron sputtering technology to maintain the chamber pressure at 1.8 mTorr. Turn on the DC power supply connected to the graphite sputtering target, set the power supply current to 2.5 A, the substrate bias voltage to -150 V, and the deposition temperature to room temperature to deposit an amorphous carbon layer with a thickness of 70 nm. (4) Continue to introduce xenon gas into the chamber at a flow rate of 45 sccm. Use DC magnetron sputtering technology to maintain the chamber pressure at 1.8 mTorr. Turn on the DC power supply connected to the chromium sputtering target. Set the power supply current to 3.0 A, the substrate bias voltage to -100 V, and the deposition temperature to room temperature. Deposit a chromium metal layer with a thickness of 80 nm. (5) Repeating steps (3) and (4), alternately depositing an amorphous carbon layer and a chromium metal layer, for a total of 20 cycles; (6) Continue to introduce xenon gas into the chamber at a flow rate of 45 sccm. Use DC magnetron sputtering technology to maintain the chamber pressure at 1.8 mTorr. Turn on the DC power supply connected to the graphite sputtering target, set the power supply current to 2.5 A, the substrate bias voltage to -150 V, and the deposition temperature to room temperature to deposit an amorphous carbon functional layer with a thickness of 220 nm. (7) The prepared amorphous carbon composite coating was placed in an atomic layer deposition chamber, and nitrogen was introduced for 2 seconds, trimethylaluminum for 6 seconds, nitrogen for 3 seconds, water vapor for 1 second, and nitrogen for 2 seconds in sequence. A total of 50 cycles were deposited, and the thickness of the ALD sealing layer was 15 nm.

[0059] In a simulated 1500 m deep sea environment, the wear-resistant coating for deep sea environment prepared in Comparative Example 2 was tested, and the corrosion current density was 3.29×10 -7 A / cm 2 After corrosion, the coating porosity is 1.61%, the friction coefficient is 0.073, and the wear rate is about 8.5×10 -9 mm 3 / Nm.

[0060] As a comparative example of Example 1, Comparative Example 1 did not perform pore sealing during the deposition of the amorphous carbon / chromium soft and hard multilayer, while the thickness of the pore sealing layer of Comparative Example 2 was relatively thin.

[0061] Figure 1 As shown, a schematic diagram of the sealing process provided by a specific embodiment of the present invention is shown, wherein the amorphous carbon composite coating is placed in an atomic layer deposition system, and dry gas (N2), gaseous precursor (TMA / TIPT), dry gas (N2), water vapor (H2O), and dry gas (N2) are introduced in sequence in a single deposition cycle.

[0062] Figure 2 As shown in the polarization test result diagram of the coating prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention, Figure 2 It can be seen that the corrosion current density of Example 1 in 15MPa simulated seawater is 1.39×10 -9 A / cm 2 The corrosion current density of the sample in comparative example 1 in 15 MPa simulated seawater is 9.25×10 -7 A / cm 2 The corrosion current density of the sample in comparative example 2 in 15 MPa simulated seawater is 3.29×10 -7 A / cm 2 Compared with the two comparative examples, the corrosion current density of Example 1 is the smallest, which decreases by 1-2 orders of magnitude.

[0063] Figure 3 As shown in the constant potential polarization test result diagram of the coating prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention, Figure 3 It can be seen that the average corrosion current density of Example 1 in 15MPa simulated seawater is 0.98nA / cm 2 The average corrosion current density of the sample in comparative example 1 in 15MPa simulated seawater is 353nA / cm 2 The average corrosion current density of the sample in comparative example 2 in 15MPa simulated seawater is 22.2nA / cm 2 , compared with the two comparative examples, the average corrosion current density of Example 1 is the smallest, which decreases by 2-3 orders of magnitude; Figure 4-Figure 6 The surface morphologies of Example 1, Comparative Example 1, and Comparative Example 2 after corrosion tests are shown respectively. The analysis using an optical microscope shows that the coating prepared in Example 1 has no obvious defects after corrosion and is more dense. After calculation, the porosity of the coating prepared in Example 1 is 0.008%, and the porosities of the coatings prepared in Comparative Example 1 and Comparative Example 2 are 3.44% and 1.61%, respectively. Compared with the two comparative examples, the porosity of Example 1 is reduced by three orders of magnitude; Figure 7 As shown, the friction coefficient of the coating prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention is Figure 7 It can be seen that the friction coefficient of the coating prepared in Example 1 is very stable, stable at about 0.062; the friction coefficient of the coating prepared in Comparative Example 1 increases significantly from 0 to 300 seconds, gradually stabilizes after 300 seconds, and stabilizes at about 0.078; the friction coefficient of the coating prepared in Comparative Example 2 is stable at 0.073. Compared with the two comparative examples, the friction coefficient of Example 1 is the smallest and is reduced by nearly 20%; Figure 8 As shown, the wear rates of the coatings prepared in Example 1, Comparative Example 1 and Comparative Example 2 after abrasion are as follows: Figure 8 It can be seen that the wear rate of the coating prepared in Example 1 is 2.3×10 -9 mm 3 / Nm, which is the lowest wear rate among the three coatings; the wear rate of the coating prepared in comparative example 1 is 1.1×10 -8 mm 3 / Nm; the wear rate of the coating prepared in Comparative Example 2 is 8.5×10 -9 mm 3 / Nm. Compared with the two comparative examples, the wear rate of Example 1 is reduced by one order of magnitude.

[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A wear-resistant coating for deep sea environment, characterized in that: The wear-resistant coating comprises an amorphous carbon composite coating and an aluminum oxide sealing layer. The aluminum oxide sealing layer is deposited on the amorphous carbon composite coating by atomic layer deposition technology and fills the internal defects of the amorphous carbon composite coating. The thickness of the aluminum oxide sealing layer is 25-120nm.

2. The wear-resistant coating according to claim 1, characterized in that: The composite coating comprises: a first metal layer and a nitride layer of the first metal sequentially deposited on the substrate; Iterative layers of an amorphous carbon layer and a second metal layer deposited on the nitride layer of the first metal, the number of the iterative layers being ≥ 6; an amorphous carbon functional layer deposited on the iterative layer; The metals in the first metal layer, the first metal nitride layer and the second metal layer are carbide-forming elements.

3. The wear-resistant coating according to claim 2, characterized in that: The metal in the first metal layer, the first metal nitride layer and the second metal layer is at least one of Cr, W, Ti, Ta, Zr, V and Nb; and / or, the thickness of the first metal layer and the first metal nitride layer is 120-180 nm; And / or, the thickness of the amorphous carbon layer is 70-90 nm; And / or, the thickness of the second metal layer is 90-110 nm; And / or, the thickness of the amorphous carbon functional layer is 230-250 nm; And / or, the substrate is any one of 17-4 PH stainless steel, S32205 duplex stainless steel and AISI 4140 alloy steel.

4. The method for preparing the wear-resistant coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. In an inert gas atmosphere, sputtering a metal target of a carbide-forming element, depositing a first metal layer on a substrate, and then introducing nitrogen to form a first metal layer / a nitride layer of the first metal; S2, sputtering a graphite target in an inert gas atmosphere to deposit an amorphous carbon layer on the first metal nitride layer in step S1; closing the graphite target, opening the metal target, and depositing a second metal layer on the amorphous carbon layer in an inert gas atmosphere, repeatedly sputtering the graphite target and the metal target to form an iterative layer of amorphous carbon layer / second metal layer; S3, sputtering the graphite target in an inert gas atmosphere to deposit an amorphous carbon functional layer on the iterative layer in step S2 to obtain an amorphous carbon composite coating; S4. Using atomic layer deposition technology, deposit an aluminum oxide sealing layer on the amorphous carbon composite coating in step S3. The aluminum oxide sealing layer fills the internal defects of the composite coating to obtain a wear-resistant coating for deep-sea environment.

5. The method for preparing the wear-resistant coating according to claim 4, characterized in that: The sputtering in steps S1, S2 and S3 adopts DC magnetron sputtering; And / or, the inert gas in step S1 is any one of helium, neon, argon, krypton and xenon; And / or, in step S1, the deposition process of the first metal layer and the first metal nitride layer is: the power of the metal target is 1.5-3.5kW, the flow rate of the inert gas is 45-65sccm, the deposition chamber pressure is 1.9-2.1mTorr, the negative bias voltage of the substrate is 100-200V, and the deposition temperature is 120-200°C.

6. The method for preparing the wear-resistant coating according to claim 4, characterized in that: Step S1: Before depositing the first metal layer, the substrate is first etched. The etching process is as follows: in an inert gas atmosphere, an ion source is used to etch the substrate for 10-50 minutes. The current of the ion source is 0.1-0.4 A. The chamber pressure of the etching is 1.5-4.5×10 -5 Torr or less, the flow rate of the inert gas is 25-43 sccm, and the negative bias voltage of the substrate is 50-250 V.

7. The method for preparing the wear-resistant coating according to claim 4, characterized in that: The deposition process of the amorphous carbon layer in step S2 is as follows: the power supply current of the graphite target is 2.5-3.5A, the gas pressure of the deposition chamber is 1.9-2.4 mTorr, the negative bias voltage of the substrate is 100-200 V, the flow rate of the inert gas is 50-65 sccm, and the deposition time is 3-5 min; And / or, in step S2, the deposition process of the second metal layer is: the power of the metal target is 2-3 kW, the power current is 2.5-3.5 A, the gas pressure of the deposition chamber is 1.9-2.1 mTorr, the negative bias voltage of the substrate is 100-200 V, the flow rate of the inert gas is 50-65 sccm, and the deposition time is 4-6 min; And / or, the number of repetitions in step S2 is 6-30 times.

8. The method for preparing the wear-resistant coating according to claim 4, characterized in that: The deposition process of the amorphous carbon functional layer in step S3 is as follows: the current of the graphite target is 2.5-3.5 A, the flow rate of the inert gas is 50-55 sccm, the pressure of the deposition chamber is 1.9-2.1 mTorr, the negative bias voltage of the substrate is 100-200 V, and the deposition temperature is room temperature.

9. The method for preparing the wear-resistant coating according to claim 4, characterized in that: The deposition process of the alumina sealing layer in step S4 is as follows: in an atomic layer deposition system in which the amorphous carbon composite coating is placed, dry inert gas, gaseous precursor, dry inert gas, water vapor, and dry inert gas are sequentially introduced in a single deposition cycle, wherein the precursor is trimethylaluminum or tetraisopropyl titanate, and the deposition cycle is repeated 100-500 times.

10. The method for preparing the wear-resistant coating according to claim 9, characterized in that: The dry inert gas is nitrogen or argon; And / or, the time for first introducing the dry inert gas is 3-6s; And / or, the introduction time of the gaseous precursor is 6-9s; And / or, the time for introducing the dry inert gas for the second time is 4-5s; And / or, the water vapor is introduced for a time of 1-4 s; And / or, the time for introducing the dry inert gas for the third time is 2-5s.

Citation Information

Patent Citations

  • Deep sea environment corrosion-resistant coating and preparation method thereof

    CN113981395A

  • Graphene film and method for converting in-situ amorphous carbon into graphene film

    CN115011922A